Can platform use patterns be an indicator of HIV-related risk and sub-group heterogeneity among men who have sex with men in Singapore: a latent class analysis - Tavitian-Exley, Isabel; Hao, Ying; Chen, Mark I-C.; Wong, Chen Seong; Kwok, Chronos; Toh, Matthias Paul Han Sim (Frontiers in Public Health, 2024)
Low-level HIV epidemic settings like Singapore face the challenge of reaching men at-risk who have less contact with programmes. We investigated patterns of meeting platform use by men seeking male sexual partners (MSM) as potential marker of risk to differentiate sub-groups for interventions. Latent Class Analysis (LCA) was applied to a survey sample of MSM recruited from bars/clubs, saunas and a smartphone application, using purposive sampling. The best-fit LCA model which identified homogeneous sub-groups with similar patterns of meeting platform was factored in multivariable regression to identify associations with risk behaviours on the pathway to HIV infection. Overall 1,141 MSM were recruited from bars/clubs (n=426), saunas (n=531) and online (n=184). Five patterns emerged, reflecting salient platform use characteristics: Sauna-centric (SC; n=413), App-centric (AC, n=276), Multiple-Platforms (MP; n=123), Platform-inactive (PI; n=257) and “Do not hook up” (DNH; n=72) classes. Men in the SC and MP classes had high probabilities of using saunas to meet partners; SC were older and less likely to have disclosed their sexual orientation. The MP class had high probabilities of connecting across all platforms in addition to saunas– and more likely to have disclosed their sexual orientation, than the PI class. Men in the SC and MP classes had twice the odds of reporting multiple sex partners (aORSC=2.1; 95%CI: 1.3-3.2; aORMP=2.2; 95%CI: 1.1-4.6). Single/non-partnered MSM and those using alcohol/drugs during sex had 1.7 (95%CI: 1.2-2.5) and 3.2 (95%CI: 2.0-5.1) the odds respectively, of reporting multiple sex partners. The SC and MP classes had higher odds of engaging in group sex while MSM using alcohol/drugs during sex had twice the odds of reporting group sex. MSM using alcohol/drugs during sex had twice the odds of reporting group sex. Alcohol/drugs and group sex were independently associated with condomless sex (as was lower education). Group sex, alcohol/drugs during sex, disclosure of sexual orientation or being Singaporean/ permanent resident were associated with recent testing for HIV. The five distinct risk profiles identified can help tailor differentiated HIV interventions, combined with field knowledge and other prevention, to expand HIV self-testing, Pre-Exposure Prophylaxis and other services (eg. Mpox vaccination) to sub-groups at risk.